Electronic Health Record Downtime Events of a Hospital: A Retrospective Analysis from Adverse Event Reports - Fang, Qichuan; Liang, Jun; Xiang, Peng; Zhao, Min; He, Yunfan; Zhang, Zijiao; Wan, Haofeng; Hu, Yue; Wang, Tong; Lei, Jianbo (Applied Clinical Informatics, 2025)
The widespread adoption of health information technology (HIT) has deepened hospitals' reliance on electronic health records (EHR). However, EHR downtime events, which refer to partial or complete system failures, can disrupt hospital operations and threaten patient safety. Systematic research on HIT downtime events in China remains limited.This study aims to identify and classify reported EHR downtime events in a Chinese hospital, assess their frequency and severity, and propose improvement recommendations and response strategies.We identified and coded downtime events based on a Chinese hospital's adverse event reports between January 2018 and August 2022, extracting features such as time, type, and affected scope. Both descriptive and inferential statistics were used for analysis.A total of 204 EHR downtime events were identified, with 96.1% (n = 196) unplanned. The most frequent categories were medication-related events (n = 52, 25.5%), imaging-related events (n = 35, 17.2%), and accounting and billing-related events (n = 17, 8.3%). For severity, 76.0% (n = 155) of events were reported as patient care disruptions, while 76.5% (n = 156) occurred within certain departments. In terms of time, the daily downtime incidence was 0.142 (95% CI: 0.122–0.164) on weekdays versus 0.064 (95% CI: 0.044–0.090) on weekends, with an incidence rate ratio (IRR) of 2.22 (95% CI: 1.52–3.25). The downtime incidence during the morning period was 0.0130 per hour (95% CI: 0.0107–0.0156), which was higher than other time periods, with IRRs ranging from 1.42 (95% CI: 1.06–1.90) to 22.2 (95% CI: 12.66–38.92).In this study, analysis of EHR downtime events in a Chinese hospital identified three key issues: high-risk downtime in medication processes, peak occurrence periods on weekdays and during morning hours, and significant clinical care disruptions. Recommended measures include implementing tiered contingency protocols, enhancing technical resilience, and establishing standardized reporting mechanisms.
Keywords: downtime; electronic health records; health information technology; patient safety; accident prevention